Sosialisasi Pemilu Damai dalam Memberikan Pemahaman Sikap Anti Politik Uang dan Anti Golput Bagi Pemuda Desa Pomah - Lati, Gustina Aruming Sekar; Saputro, Nur Ahmad; Jabbar, Abdul (Jurnal Dharma Indonesia, 2024)
Pomah Village is one of the villages located in Klaten Regency, Central Java, which is one of the locations held by UNNES GIAT 7. At this time, young voters have an important role in determining their voting rights for the political contestation process. However, not all young people understand and are aware of the importance of political education. Therefore, UNNES GIAT 7 students came up with the idea of a work program in the form of "Peaceful Election Outreach, Anti-Money Politics and Anti-Abstention" to provide an understanding to young voters about the importance of using their voting rights and also anticipate all kinds of actions that deviate from democratic values by avoiding the practice of money politics and abstention. Money politics usually occurs before the election with the mode of regional head candidates or legislative members giving money, basic necessities, rewards and others to the community, so it is consciously considered a corrupt practice. Money politics directly violates the provisions of the UUD 1945 28E paragraph (2). In practice, money politics makes people unable to make choices based on their conscience because they have received rewards from candidates. Therefore, the outreach of peaceful elections can help provide solutions for the community to increase awareness of political participation by implementing rights and obligations and implementing anti-money politics and anti-abstention attitudes in political contestation.